(untitled) (Journal of Dhaka Medical College, 2020)
Background: Assessment of severity in patients with Chronic Obstructive Pulmonary Disease(COPD) is usually done at rest by spirometry test. But cardiopulmonary exercise test can be a measure to assess the functional capacity more accurately in patients with COPD. Method: Fifty eight patients with stable COPD were included in this study period of one and half years from January 15 to June 2016 and categorise into four groups based on spirometric data following the GOLD guidelines 2018; GOLD 1 mild COPD, GOLD 2 moderate COPD, GOLD 3 severe COPD and GOLD 4 very severe COPD. Symptom limited CPET on treadmill using Bruce protocol using cardiopulmonary exercise machine was done in all fifty eight patient. Results: twenty one patients (36.20%) had moderate COPD; twenty six(44.82%) had severe COPD; eleven(18.96%) had very severe COPD and none found to be categorised as mild COPD. All fifty eight patients attained anaerobic threshold. Majority(34, 58.62%) of patients stopped exercise due to shortness of breath; decreased oxygen saturation was the cause of stopping exercise in eight(13.7%) patients; other causes of exercise limitation were increased heart rate, vertigo, leg fatigue, increased blood pressure, ventricular ectopic and chest tightness. Four patients were found to limit exercise due to combined shortness of breath and leg fatigue. A significant correlation between forced expiratory volume in first second (FEV1, percent predicted) and maximum oxygen uptake(ml/kg/min) was observe. Twenty(46.55%) patients with low(<40%) AT were identified who could be benefited from pulmonary rehabilitation program. Conclusion: CPET can be useful to identifying the COPD patients with functional capacity impairment for pulmonary rehabilitation by assessing exercising capacity and the cause of exercise limitation. J Dhaka Medical College, Vol. 28, No.1, April, 2019, Page 23-27